2014
DOI: 10.1111/cge.12420
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐thalassemia intellectual disability: variable phenotypic expression among males with a recurrent nonsense mutation – c.109C>T (p.R37X)

Abstract: Alpha-thalassemia intellectual disability, one of the recognizable X-linked disability syndromes, is characterized by short stature, microcephaly, distinctive facies, hypotonic appearance, cardiac and genital anomalies, and marked skewing of X-inactivation in female carriers. With the advent of next generation sequencing, mutations have been identified that result in less severe phenotypes lacking one or more of these phenotypic manifestations. Here we report five unrelated kindreds in which a c.109C>T (p.R37X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…X-linked intellectual disability (XLID) refers to forms of ID typically associated with X-linked recessive inheritance. Mutations in monogenic XLID have been reported in >100 genes, many of which are now used in routine diagnostic screening panels (Basehore et al, 2015 ). Despite screening for mutations in selected known XLID genes by conventional linkage/candidate gene analysis or array CGH for examining copy number variants (CNVs), large number of families mapping to the X-chromosome remained unresolved (Lubs et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…X-linked intellectual disability (XLID) refers to forms of ID typically associated with X-linked recessive inheritance. Mutations in monogenic XLID have been reported in >100 genes, many of which are now used in routine diagnostic screening panels (Basehore et al, 2015 ). Despite screening for mutations in selected known XLID genes by conventional linkage/candidate gene analysis or array CGH for examining copy number variants (CNVs), large number of families mapping to the X-chromosome remained unresolved (Lubs et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Usually pathological mutations in the ATRX gene are associated with a large and clinically heterogeneous spectrum of X-linked mental deficiency syndromes 16 . However, with the advent of next generation sequencing, mutations have been identified resulting in less severe phenotypes lacking one or more of ATRX syndrome phenotypic features 17 . In this present study, the diagnosis of HbH performed in patient II-3 was based on the haemoglobin H inclusion body stain (brilliant cresyl blue) and the high performance liquid chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoblots of extracts from patient-derived EBV-transformed B-lymphocytes showed significantly reduced levels of ATRX protein from all patients tested (McDowell et al, 1999;Cardoso et al, 2000). Interestingly, in patients with early premature stop codons (e.g., p.Arg37X), translation was initiated from an internal methionine that produced a smaller truncated protein at ∼30% levels leading to a milder phenotype (Howard et al, 2004;Abidi et al, 2005;Basehore et al, 2015). Utilizing recombinant proteins, other studies demonstrated that mutations within the ATPase domain attenuated ATPase activity but did not reduce it, while mutations in the ADD domain or the PML-targeting domain reduced localization to chromocenters and PML nuclear bodies, respectively (Cardoso et al, 2000;Bérubé et al, 2008).…”
Section: Delineating Pathophysiological Mechanisms Of the Atr-x Syndrmentioning
confidence: 99%